RENAL VASCULAR ENDOTHELIUM RESPONSE IN RATS WITH GLOMERULONEPHRITIS IN CRYOCONSERVED PLASCENT IMPLANTATION - Kapustyanska, A.A. (World of Medicine and Biology, 2019)
Today, literature data testify to a growth in pathology of the autoimmune genesis. Among the formidable forms of autoimmune pathology, glomerulonephritis is recorded. The purpose of our work was to study the impact of a single injection of cryopreserved placenta on the vascular endothelium status of the kidney in experimental autoimmune glomerulonephritis. In animals of both groups on the 7th day of the experiment, vascular dilatation, uneven enlargement of their lumens, vascular congestion and numerous small erythrostates, with thrombosis and hemorrhages were revealed. In the experimental group of animals, moderate and small focal perivascular lymphocyte infiltration of the stroma was observed, against which the phenomenon of weak atrophy of the tubular epithelium was observed. There are almost no signs of fibrosis and sclerotic changes in interstitial connective tissues. In the control group, on the 30th day of the experiment, there were numerous spread areas sclerosal interstitium with signs of diffuse lymphohistocytic infiltration, against the background of which, there were significant dystrophic cell changes and clear phenomena of tubular epithelium atrophy. In peritubular hemocapillaries, signs of the vascular wall sclerosing and erythrostasis were revealed. In animals of the experimental group, some expansion of interstitium with signs of perivascular edema was found, as well as moderate lymphohistocytic infiltration of the stroma, on the background of which small foci of the tubular epithelium atrophy and isolated areas of interstitium sclerosis were identified. Most of the renal tubules had dystrophic changes in the epithelial cells.
Keywords: kidney; autoimmune glomerulonephritis; rats; cryopreserved placenta